HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KELENTUKAN OTOT PUNGGUNG TERHADAP PUKULAN LOB CLUB BULUTANGKIS PUTRA RAMA-RAMA JUNIOR - Toni Lumban Batu; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on observations from research at the junior rama’s men's badminton club, there are still many players in lobes that usually do not reach the goal, and the flexibility of the back muscles is less flexible, allowing stiffness when making punches and shuttles easily the opponent can be taken. the aim of this study was to determine the relationship between the muscle strength of the shoulder arm and the flexibility of the back muscles with the bunt of the badminton lobclub. The population in this research consisted of all male badminton juniors who became with a total of 10. Samples in this study were 10 people using total sampling techniques. The tools in this research were Expanding Dynamometer, hyper extension test and lob punch ability. The data obtained was analyzed using the product moment correlation. Based on the analysis of normality test data, X1 produces Lcount of 0.132 and Ltable 0.258 and X2 produces Lcount of 0.163 and Ltable 0.258. while the variable Y yields a Lcount of 0.144 and an Ltable of 0.258. This means Lcount <LTable. Based on statistical data analysis, the data is normally distributed. Based on the test requirements of the above analysis, the hypothesis test on the variables X1 and X2 against the Y variable data is 0.809> 0.798 Rhitung> Rtabel data. Thus, there is a joint relationship between the strength of the shoulder arm muscles and the back muscle flexibility of the badminton club. for men young junior.Key Words: Arm and shoulder muscle strength, Back muscle strength, Lop Punch Ability